1998
DOI: 10.1042/bj3330631
|View full text |Cite
|
Sign up to set email alerts
|

The broad specificity of dominant inhibitory protein kinase C mutants infers a common step in phosphorylation

Abstract: Dominant negative properties are conferred on protein kinase (PK) Calpha by mutation of the phosphorylation site in the activation loop of the kinase domain. To address the universality and/or specificity of such mutations, analogous alterations were introduced in other members of the PKC family and tested for their effects on the function of co-transfected activated PKC. For all three subclasses of the PKC family, mutations of the predicted activation loop phosphorylation sites resulted in dominant negative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 38 publications
4
46
1
Order By: Relevance
“…4B). PI 3-kinase has already been demonstrated to play a role in PKC phosphorylation through its activation of phospholipid-dependent kinase 1 (7,8). Our findings also implicate PI 3-kinase in the control of PKC⑀ dephosphorylation and degradation.…”
Section: Serum and Readhesion Are Required For The Formation Of Pkc⑀supporting
confidence: 65%
“…4B). PI 3-kinase has already been demonstrated to play a role in PKC phosphorylation through its activation of phospholipid-dependent kinase 1 (7,8). Our findings also implicate PI 3-kinase in the control of PKC⑀ dephosphorylation and degradation.…”
Section: Serum and Readhesion Are Required For The Formation Of Pkc⑀supporting
confidence: 65%
“…Taken together, these data indicate that PKC positively regulates p70S6K through a concerted effect with other p70S6K regulators and that the inhibitory effects of PKC K/W are due to a lack of positive function rather than to sequestration of upstream p70S6K activators. Recently, it was reported that a kinase-inactive mutant of PKC containing a mutation in its activation loop (threonine 410 mutated to alanine) can antagonize PKCε and PKC␣ activities due to a common activation mechanism (20). We found that PKC K/W did not affect activation of p70S6K by PMA (data not shown), which activates conventional and/or novel PKCs but not atypical isoforms, such as PKC and -.…”
Section: Discussionmentioning
confidence: 61%
“…8). The control using a corresponding PKC mutant had no consequence on G Cl,swell , thereby eliminating the possibility of a promiscuous effect, for instance, due to sequestration of upstream kinases such as PDK1, essential for activation of several PKCs (52). It should be noted that the PKC mutant displayed slower G Cl,swell activation in comparison to non-transfected cells (see Fig.…”
Section: Discussionmentioning
confidence: 99%